Functional and Integrative Analysis of the Proteomic Profile of Radish Root under Pb Exposure - Wang, Yan; Xu, Liang; Tang, Mingjia; Jiang, Haiyan; Chen, Wei; Zhang, Wei; Wang, Ronghua; Liu, Liwang (Frontiers in Plant Science, 2016)
Lead (Pb) is one of the most abundant heavy metal pollutants, which can penetrate the plant through the root and then enter the food chain causing in potential health risks for human beings. Radish is an important root vegetable crop worldwide. To investigate the mechanism underlying plant response to Pb stress in radish, the protein profile changes of radish roots were comprehensively analyzed using iTRAQ (Isobaric Tag for Relative and Absolute Quantification) respectively upon Pb(NO3)2 at 500 mg L-1(Pb500) and Pb(NO3)2 at 1000 mg L-1(Pb1000) exposure. A total of 3, 898 protein species were successfully detected and 2,141 were quantified. Among them, a subset of 721 protein species were differentially accumulated upon at least one Pb treatment, and 135 ones showed significantly abundance changes during both two Pb-stressed conditions. Many critical protein species related to protein translation, processing, and degradation, reactive oxygen species (ROS) scavenging, photosynthesis and respiration and carbon metabolism were successfully identified. Gene Ontology (GO) and pathway enrichment analysis of the 135 differential abundance protein species revealed that the overrepresented GO terms were include in ‘cell wall’, ‘apoplast’, ‘response to metal ion’, ‘vacuole’ and ‘peroxidase activity’, and the critical enriched pathways were involved in ‘citric acid (TCA) cycle and respiratory electron transport’, ‘pyruvate metabolism’, ‘phenylalanine metabolism’, ‘phenylpropanoid biosynthesis’ and ‘carbon metabolism’. Furthermore, the integrative analysis of transcriptomic, miRNA, degradome, metabolomic and proteomic data provided a strengthened understanding of radish response to Pb stress at multiple levels. Under Pb stress, many key enzymes (i.e. ATP citrate lyase, Isocitrate dehydrogenase, fumarate hydratase and malate dehydrogenase) involved in the glycolysis and TCA cycle were severely affected, which ultimately cause alteration of some metabolites including glucose, citrate, and malate. Meanwhile, a series of other defense responses including ascorbate (ASA)–glutathione (GSH) cycle for ROS scavenging and Pb-defense protein species (glutaredoxin, aldose 1-epimerase malate dehydrogenase and thioredoxin), were triggered to cope with Pb-induced injuries. The results would be helpful for further dissecting molecular mechanism underlying plant response to HM stresses, and facilitate effective management of HM contamination in vegetable crops by genetic manipulation.